Causes of death in men with localized prostate cancer: a nationwide, population‐based study. (15th May 2015) - Van Hemelrijck, Mieke; Folkvaljon, Yasin; Adolfsson, Jan; Akre, Olof; Holmberg, Lars; Garmo, Hans; Stattin, Pär
Abstract : Objective: To detail the distribution of causes of death from localized prostate cancer (PCa). Patients and Methods: The database PCBase Sweden links the Swedish National Prostate Cancer Register with other nationwide population‐based healthcare registers. We selected all 57 187 men diagnosed with localized PCa between 1997 and 2009 and their 114 374 PCa‐free control subjects, matched according to age and county of residence. Mortality was calculated using competing risk regression analyses, taking into account PCa risk category, age and Charlson comorbidity index (CCI). Results: In men with low‐risk PCa, all‐cause mortality was lower compared with that in corresponding PCa‐free men: 10‐year all‐cause mortality was 18% for men diagnosed at age 70 years, with a CCI score of 0, and 21% among corresponding control subjects. Of these cases, 31% died from cardiovascular disease (CVD) compared with 37% of the corresponding control subjects. For men with low‐risk PCa, 10‐year PCa‐mortality was 0.4, 1 and 3% when diagnosed at age 50, 60 and 70 years, respectively. PCa was the third most common cause of death (18%), after CVD (31%) and other cancers (30%). By contrast, PCa was the most common cause of death in men with intermediate‐ and high‐risk localized PCa. Conclusions: Men with low‐risk PCa had lower all‐cause mortality than PCa‐free men because of lower CVD mortality, driven by early detection selection; however, for men with intermediate‐ or high‐risk disease, the rate of PCa death was substantial, irrespective of CCI score, and this was even more pronounced for those diagnosed at age 50 or 60 years.